Home Gardening and the Health and Well-Being of Adolescents. Issue 1 (January 2017) - van Lier, Laila E.; Utter, Jennifer; Denny, Simon; Lucassen, Mathijs; Dyson, Ben; Clark, Terryann
Background. The current article explores the associations between home gardening and dietary behaviors, physical activity, mental health, and social relationships among secondary school students in New Zealand. Method. Data were drawn from a national youth health and well-being survey, conducted in 2012. In total, 8, 500 randomly selected students from 91 randomly selected secondary schools completed the survey. Results. Two thirds of students had a vegetable garden at home and one quarter of all students participated in home gardening. Students participating in gardening were most likely to be male, of a Pacific Island ethnicity, of younger age, and living in a rural area. Gardening was positively associated with healthy dietary habits among students, such as greater fruit and vegetable consumption. Gardening was also positively associated with physical activity and improved mental health and well-being. Students who participate in gardening report slightly lower levels of depressive symptoms and enhanced emotional well-being and experience higher family connection than students who do not participate in gardening. Conclusions. Gardening may make a difference for health and nutrition behaviors and may contribute to adolescents' health and well-being in a positive manner. Health promoters should be encouraged to include gardening in future interventions for young people.